Evaluation of Factors Affecting Enuresis in 6- to 12-Year-Old Children Referred to the Pediatric Nephrology Clinic - Azarfar, Anoush; Ghodsi, Alireza; Faravani, Farnoosh; Ghahremani, Sara (Journal of Child Science, 2021)
Enuresis is one of the most common disorders in children, and if left untreated can cause anxiety, low self-esteem, and family problems. The aim of this study was to investigate the factors associated with enuresis to provide recommendations for more efficient prevention and treatment. A cross-sectional study was performed on children aged 6 to 12 years with enuresis, referred to the pediatric clinic between April 2017 and April 2018. Children were divided into two groups: monosymptomatic enuresis and healthy subjects. Then, a questionnaire was completed by their parents to assess the factors related to enuresis. The data were analyzed using SPSS software. In this study, out of 140 children with an average age of 8.22 ± 2.01 years, 77 cases (55%) had enuresis, of which 57 (40.7%) had primary enuresis, and 20 cases (14.3%) had secondary enuresis. There was a significant difference between the control and the case groups in terms of: father's education, family income, family history, number of people sleeping in the room, family problems, problems at school, history of urinary tract infections, history of pinworms, difficulty falling asleep, difficulty in waking up, feeling tired after waking up, and drowsiness during the day. Enuresis is associated with several physiological, psychological, and genetic factors. Controlling these factors requires paying attention to the elements such as the mental health of the family and child's sleep health through education, family awareness, and counseling.
Keywords: enuresis; factors; drowsiness; children